The impact of 11/13 Paris terrorist attacks on stock prices: evidence from the international defence industry. Issue 1 (2nd January 2017) - Apergis, Emmanuel; Apergis, Nicholas
ABSTRACT: This study explores the effect of the Paris terrorist attacks on the stock returns and the volatility for the most important companies in the global defence industry. To this end, it employs the General Autoregressive Conditional Heteroscedasticity methodology. The findings clearly indicate that this terrorist event has a positive impact on both the returns and the volatility of these stocks.